Race-related Stress and its Correlations with Preterm Births, Rapid Births, and Low Birth Weights - Ronae Kashawna McLin (The Journal of Undergraduate Research, 2013)
Abstract The purpose of this project was to determine the factors that cause African Americans to have the highest rates of infant mortality and pregnancy complications. It was hypothesized that the presence of significant race-related stress during or before an African American woman’s pregnancy will result in an African American woman’s higher susceptibility to preterm births, rapid births, and low birth weights. The respondents of the study, nine in total, were women of the Moms2B program, a program aimed to reduce infant mortality by providing educational services in regards to healthy childbearing. All of the women had African American heritage and resided in Weinland Park, Ohio. The survey utilized for the project consisted of 14 questions, including two questions with two parts. Over the duration of two weeks, nine surveys were collected. Two women out of the nine, claimed to have experienced preterm labor during their pregnancy. In the survey, the women were asked to list the most significant stressors during their pregnancy. Stressors with the highest amount of selections, n=5, were ‘lack of support’. Following in second were: ‘Employment’, ‘Family matters’, ‘The Future’, and ‘Romantic relationships’ all with four selections. The hypothesis was unable to be accepted or rejected due to the lack of surveys completed. For this reason, data received was considered statistically insignificant. The data received did not assist in coming to a conclusion for the experiment. The future of the project will be dependent on the submittal of the survey to the Institutional Review Board of The Ohio State University’s School of Nursing.